The evolution of crystalline ordering for ligand-ornamented zinc oxide nanoparticles. Issue 12 (3rd March 2016) - Zobel, Mirijam; Windmüller, Anna; Schmidt, Ella M.; Götz, Klaus; Milek, Theodor; Zahn, Dirk; Kimber, Simon A. J.; Hudspeth, Jessica M.; Neder, Reinhard B.
Abstract : In situ total scattering reveals influence of organic ligands and reaction path control onto disorder and crystallization in nucleating ZnO nanoparticles. Abstract : Recent total scattering experiments have opened up the possibility to study nanoparticle formation in situ and to observe the structural transformation from precursor clusters to adult particles. Organic ligand molecules interact with precursors of metal oxide nanoparticles, yet their influence onto the evolution of crystallinity during particle formation has not been addressed in detail; nor have in situ total scattering experiments ventured into the field of low-concentration, room-temperature syntheses in organic solvents to date. In this report, we follow the crystallization of ZnO nanoparticles in ethanol in the presence of different organic ligands. Low coordinated zinc precursor clusters rapidly polymerize upon base addition to particles of ca. 1 nm in diameter. In situ SAXS experiments reveal that the overall particle size increases to 2 to 4 nm with advancing reaction time. Complementary in situ PDF experiments show smaller crystalline domain sizes, which are only one third to half as large as the particle diameter. The ZnO particles thus feature a crystalline core surrounded by a disordered shell. Both, the core and the shell diameter are influenced by the different surface-bound organic ligands, which prevent an immediate relaxation to fully crystalline particles. A slow crystallization takes place in solution. We assume a dynamic equilibrium of the ligand and solvent molecules at the particle surface, which enables gradual bond restructuring. With suitably adjusted synthesis conditions, in our case by a continuous base addition, we show how to bypass the disordered intermediates, allowing the spontaneous nucleation of fully crystalline nanoparticles.